2013
DOI: 10.1111/den.12076
|View full text |Cite
|
Sign up to set email alerts
|

Dense‐type crypt opening seen on magnifying endoscopy with narrow‐band imaging is a feature of gastric adenoma

Abstract: Determining the number of CO visualized in superficial elevated-type gastric neoplasias by ME-NBI appears to be a useful method for discriminating between LGA and EGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Studies were excluded if they were not original reports on the diagnosis of EGC or if they were case reports. After this filtering, 66 articles were selected for use in this algorithm (57 from PubMed and nine from the manual search) …”
Section: Methodsmentioning
confidence: 99%
“…Studies were excluded if they were not original reports on the diagnosis of EGC or if they were case reports. After this filtering, 66 articles were selected for use in this algorithm (57 from PubMed and nine from the manual search) …”
Section: Methodsmentioning
confidence: 99%
“…However, limited data are available for the diagnosis of pelvic masses by EUS-FNA. [1][2][3][4][5] Herein, we report a case of ovarian serous adenocarcinoma diagnosed by EUS-FNA. An 82-year-old woman with cervical lymphadenopathy was admitted to Japanese Red Cross Wakayama Medical Center.…”
Section: Transrectal Endoscopic Ultrasound-guided Fine-needle Aspiratmentioning
confidence: 96%
“…These findings were quite different from those of intestinaltype adenoma. 4,5 En-bloc endoscopic submucosal dissection specimen revealed PGA (22 × 23 mm in diameter) ( Fig. 2) with a tiny…”
Section: Pyloric Gland Adenoma Observed By Magnifying Endoscopy With mentioning
confidence: 99%
“…Kanesaka et al investigated whether the visualization of CO by ME-NBI was useful for discriminating between gastric LGA and EGC retrospectively by evaluating 51 superficial elevated-type gastric neoplasia (LGA, n = 10; and EGC, n = 41). 48 They reported that visualized CO was significantly more common in the LGA group than in the EGC group (31.2 [95% CI 16.3-46.1] vs 6.3 [95% CI 3.6-9.0], P < 0.001). With a cut-off number of visualized CO of 20, the sensitivity, specificity and accuracy of dense-type CO for discriminating between LGA and EGC were 90.0%, 87.8% and 88.2%, respectively.…”
Section: Differential Diangosis Between Gastric Low-grade Adenoma (Lgmentioning
confidence: 98%
“…In addition, ME‐NBI can visualize CO as slit‐like structures in the gastric epithelial neoplasia. Kanesaka et al investigated whether the visualization of CO by ME‐NBI was useful for discriminating between gastric LGA and EGC retrospectively by evaluating 51 superficial elevated‐type gastric neoplasia (LGA, n = 10; and EGC, n = 41) . They reported that visualized CO was significantly more common in the LGA group than in the EGC group (31.2 [95% CI 16.3–46.1] vs 6.3 [95% CI 3.6–9.0], P < 0.001).…”
Section: Endoscopic Evaluation Of High‐risk Group For Gcmentioning
confidence: 99%